Mapping and Evaluating Marine Protected Areas and Ecosystem Services: A Transdisciplinary Delphi Forecasting Process Framework - Belgrano, Andrea; Novaglio, Camilla; Svedäng, Henrik; Villasante, Sebastián; Melián, Carlos J.; Blenckner, Thorsten; Bergström, Ulf; Bryhn, Andreas; Bergström, Lena; Bartolino, Valerio; Sköld, Mattias; Tomczak, Maciej; et al. (Frontiers in Ecology and Evolution, 2021)
Marine Protected Areas (MPAs) are an important tool for management and conservation and play an increasingly recognised role in societal and human well-being. However, the assessment of MPAs often lacks a simultaneous consideration of ecological and socio-economic outcomes, and this can lead to misconceptions on the effectiveness of MPAs. In this perspective, we present a transdisciplinary approach based on the Delphi method for mapping and evaluating Marine Protected Areas for their ability to protect biodiversity while providing Ecosystem Services (ES) and related human well-being benefits – i.e., the ecosystem outputs from which people benefit. We highlight the need to include the human dimensions of marine protection in such assessments, given that the effectiveness of MPAs over time is conditional on the social, cultural and institutional contexts in which MPAs evolve. Our approach supports Ecosystem-Based Management and highlights the importance of MPAs in achieving restoration, conservation, and sustainable development objectives in relation to EU Directives such as the Marine Strategy Framework Directive (MSFD), the Maritime Spatial Planning Directive (MSPD), and the Common Fisheries Policy (CFP).